Analysis of some intonation patterns of gender linguistics (Herald of Journalism, 2020)
This article analyzes the differences between male and female speech- es and emphasizes the importance of studying gender communication. The survey involves the intonation patterns of gender linguistics, that is, the differences between male and female speeches, which appear in dif- ferent aspects of language studies: phonetics, phonology and vocabulary, and so on. Cultural, social and psychological factors which are considered to be the focus of gender studies today, determine the stereotypes of male and female qualities which in turn implicitly lead to the society’s attitude towards women and men, as well as form the mechanisms of constructing the authority system based on different gender speeches. Several coef- ficients of exclamation and emphatic sentences used by women reflect a greater emotional aspect of women.
Keywords: gender studies, intonation, communicant, vocabulary.